Archiving in the Face of Erasure: the Idea of the “Post-German” Archive - Ćwiek-Rogalska, Karolina (Poznańskie Studia Slawistyczne, 2020)
The article introduces the notion of the “post-German” archive as an idea for further research on the erased cultures of Central Europe. The author questions the hierarchical and top-down structure of the institutionalized archive. Instead, she proposes to understand the “post-German” archive as an inclusive conception. It would incorporate various narratives, languages, and perspectives. In this way, the canonization of given motives can be avoided. The author pays special attention to the responsibility of the researcher. She illustrates the theoretical framework with examples from Polish and Czech archival practices.